Trilobites de la Formación San Juan (Ordovícico Inferior), Precordillera Argentina (Ameghiniana, 2014)
New trilobite species from the San Juan Forrnation, on the west fIank of the Cerro La Silla and Cerro Viejo, near Jáchal (San Juan Province), include late Tremadoc-early Arenig Leiostegium precordilleranus nov. sp., early Arenig Platillaenus niquivilensis nov. sp. and P. jaanussoni nov. sp., late Arenig-early Llanvirn Basilicus (Basiliella) leanzai nov. sp., and Waisfeldaspis beatrizae nov. gen. et sp. A new scutelluine trilobite, Waisfeldaspis nov. gen., is proposed to include a rare species with a pygidium as wide as long, axis very short. and pleural fields with only two pairs of ribs.